Xanthogranulomatous Pancreatitis Combined with Intraductal Papillary Mucinous Carcinoma In Situ - Kim, Yo Na (The Korean Academy of Medical Sciences, 2010)
Xanthogranulomatous lesion is a rare condition in which lipid-laden histiocytes are deposited at various locations in the body. Xanthogranulomatous pancreatitis (XGP) associated with an intraductal papillary mucinous tumor (IPMT) is extremely rare. In this study, we described a case of XGP associated with IPMT and include a review of the literature. A pancreatic cystic mass was detected in a 72-yr-old woman by abdominal computed tomography. Pylorus-preserving pancreaticoduodenectomy was performed and diagnosis of XGP combined with intraductal papillary mucinous carcinoma in situ was made. After 13 months of follow-up, the patient is in good health without any evidence of tumor recurrence. Although XGP associated with IPMT is rare, we suggest that such cases should be brought to the attention of clinical investigators, as it may produce clinical features that mimic pancreatic cancer.